Using a new wind turbine emulator to analyze tower shadow and yaw error effects. (15th October 2018) - Mohammadi, Ebrahim; Fadaeinedjad, Roohollah; Naji, Hamid Reza
Highlights: A new wind turbine emulator is proposed using FAST software. The emulator considers the aerodynamic, mechanical and electrical aspects of the WT. Tower shadow and yaw error effects are studied using the proposed emulator. The simulation is performed and its results are compared with the emulation results. Abstract: The majority of the available wind turbine emulators (WTEs) utilize the detailed electrical sub-systems, whereas the simplified models are considered for the other aspects. However, wind turbines (WTs) are complicated systems with different aspects that should be appropriately modeled for a realistic assessment. This paper presents a new wind turbine emulator which considers aerodynamic, mechanical, and electrical aspects of the WTs. Some tests are performed to evaluate the capabilities and limitations of the emulator; then, the proposed emulator is used to analyze the tower shadow and yaw error effects which can produce power fluctuations and fatigue loads. In addition to tower shadow effect, the yaw error which has a more severe effect is studied in this paper considering the mechanical dynamics of the WT which were not considered in literature. The proposed emulator utilizes the AeroDyn and FAST software tools to model the aerodynamic and mechanical aspects of a WT considering the real electrical sub-systems. Moreover, the tower shadow and yaw error effects are modeled in simulation and the results are compared with the emulation results. The electrical sub-systems are modeled in the MATLAB/Simulink for simulation, whereas the real mechanically coupled induction motor-induction generator set is used for the emulator.